Synthesis of 7-(Hydroxy) Coumarin and Its Activity Test As Antibacterial against Staphylococcus aureus and Shigella flexneri - Prabawati, Susy Yunita; Fitriana, Fitriana (Proceeding International Conference on Science and Engineering, 2017)
A synthesis of 7-(hydroxy)coumarin and its activity as antibacterial against Staphylococcus aureus and Shigella flexneri has been performed. The synthesis of the coumarin was carried out by reacting ethyl acetate and 2,4-dihydroxybenzaldehyde using piperidine as an alkaline catalyst via Knoevenagel reaction and antibacterial activity test was performed using disc diffusion method. The product of 7- (hydroxy)coumarin was obtained as a bright brown crystalline (m.p. 125 °C) with a rendment of 77%. The FTIR spectrum shows the absorption of -OH groups at 3101,54 cm-1 and unsaturated lactone groups at 2345.44 cm-1 which is a typical group of coumarin's derivatives. Analysis using 1H-NMR spectrometer also showed the proton of the -OH group appearing on chemical shift (?) 9.932 ppm. The antibacterial activity test showed that the compound of 7- (hydroxy) coumarin has the highest activity at 20% concentration as an antibacterial against bacteria Staphylococcus aureus and Shigella flexneri with inhibit zone was 24.55 and 20.43 mm, respectively. It means the 7-(hydroxy) coumarin compound has a strong inhibiting activity.